Penyuluhan aplikasi bahan organik eceng gondok untuk memperbaiki retensi air pada zone perakaran tanaman jagung - Nurmi, Nurmi (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
Water hyacinth is one of the organic materials that can be used to increase the organic matter content of the soil. The high organic matter content is expected to improve soil properties, particularly the soil's ability to retain water, thereby increasing water availability in the root zone. Increased water availability is a consequence of the high ability of water hyacinth organic matter to bind water, as well as the enhanced ability of the soil to infiltrate water due to the creation of good soil porosity. High water infiltration will reduce the amount of water flowing over the soil surface, potentially causing soil degradation due to erosion. It ultimately will increase water availability in the root zone. This Community Service activity aims to transfer the technology of utilising water hyacinth to increase water retention in the root zone of plants to farmers. Community service in the field is carried out through counselling and demonstrations of water hyacinth application in plantations. The results obtained indicate that the transfer of technology using water hyacinth to enhance water retention is acceptable to farmers, suggesting that the community service program can be considered a success. Farmers are very optimistic about applying what they have learned from this community service activity, as they believe the technology is straightforward to use in the field.